CORPORATE TAX AVOIDANCE AND COST OF EQUITY CAPITAL OF LISTED MANUFACTURING COMPANIES IN NIGERIA - Baba, Halima Abdullahi (Kashere Journal of Management Sciences, 2024)
Corporate tax avoidance has been a significant concern for policymakers, investors, and the public. As companies seek to minimize their tax liabilities legally, the extent to which tax avoidance affects various aspects of corporate finance remains a subject of debate. This study aims to investigate the effects of corporate tax avoidance on the cost of equity capital in Nigeria’s listed manufacturing companies. It is an empirical study with the goal of examining the relationship between tax avoidance and the cost of equity capital, a key indicator of the return investors in Nigerian listed manufacturing companies expect. The Study makes use of a quantitative research design, which entails collecting numerical data, to test hypotheses. Similarly, the study uses correlation design to ascertain the relationship between tax avoidance and the cost of equity capital in Nigeria’s listed manufacturing companies. The study population consists of seventy five (75) quoted firms on the Nigerian Exchange Group (NGX) as at 31st December 2020. The study makes use of purposive sampling technique to arrive at a sample size of 42 manufacturing companies between 2011 and 2020. The study used multiple regression analysis to test hypothesis which states that tax avoidance is negatively correlated with the cost of equity capital. The study found that, while extreme corporate tax avoidance techniques significantly increase the cost of equity capital for listed manufacturing companies in Nigeria due to information asymmetry and agency issues, tax avoidance is a viable strategy for lowering the amount of taxes paid to tax authorities. This attract negative attention from stakeholders, including shareholders, customers, and the general public. The study’s findings show that companies’ extreme corporate tax avoidance strategies will force equity investors to demand higher returns. This is as a result of information asymmetry risk. This further suggests that measures to close tax law loopholes such as legislative reforms may need to be put in place by tax regulators and other stakeholders.